Contraction based identification for nonlinear systems. Issue 28 (2015) - Pérez, A. Flores; Tang, Yu; Grave, Ileana
Abstract: A top-down approach to identification for systems with nonlinear parameterizations has been recently developed in Flores-Perez et al. (2014, 2015) based on contraction analysis where, at the top-level, the contraction analysis is carried out to ensure the proposed estimation algorithm possess the desired contraction properties, then, at the down-level, the estimation algorithm is realized through a proportional plus integral (PI) form. The realization of estimation schemes however relies on the assumption that state time derivatives are available. In this paper, by filtering signals involved in the system, an alternative to the realization of estimation algorithms without requiring the state time derivatives is given.